GERAKAN TANAH DI KARANGSAMBUNG, PENYEBAB DAN ANTISIPASI PENCEGAHANNYA - Mustofa Nur, Arief (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2007)
Land movement or better known as landslide represents one of the geologic ha-zard often occur in Indonesia including Karangsambung. Landslide basically occurs as a result of slope instability. The aim of this researh was to study factors affecting land mo-vement. The objective of this study was to determine anticipatory steps that can be per-formed by the community itself. The method used was by observation and morphological analysis of the land movement, geological aspect, hidrological aspect, and aspect of landuse. Based on the observed data and literature study, there are two types of landslide movement in Karangsambung area, i.e. creep type at small slope (3°-5°) and slump type at high slope (60°). The mechanism causing land movement in the research location is estimated to be clays that is thick enough to join each others at bedrock in the form of claystone Karangsambung Formation having the character of waterproof. Existence of o-ther factors such as inclination of slope and hidrology progressively trigger the land mo-vement. This condition caused trigger force bigger than supported force, so that the land easier to move. Anticipatory steps that can be done are by closing cracking land, preventing sur-face water enter into land movement area, making stone bagwark and bamboo, and also the people are advised to set aside to safer places if heavy rain comes.